Are men's gender equality beliefs associated with self-reported intimate partner violence perpetration? A state-level analysis of California men. - Kalysha Closson; Nicole E Johns; Anita Raj (PLoS ONE)
Objectives To assess the association between gender equality beliefs and self-reported intimate partner violence (IPV) perpetration among California men. Methods We analyzed men's data (N = 3609) from three waves (2021, 2022, and 2023) of cross-sectional data from a statewide sample of California adults. We assessed gender equality beliefs using a three-item measure adapted from the World Values Survey, with higher scores representing more gender unequal beliefs (e.g., 'On a whole, men make better political leaders than women'). We assessed IPV perpetration in the last year by asking a) whether men committed any form of violence in the last year (physical violence, use or threat of violence with a weapon, sexual violence) and b) among those who reported committing violence, who they committed violence against. Those reporting violence against "a spouse or romantic partner" were categorized as perpetrating past-year IPV. Analyses were weighted to yield population estimates. Crude and adjusted logistic regression models evaluated the association between gender equality beliefs and past-year IPV perpetration. Results Almost 2% of men-equivalent to more than 280,000 men in California-reported IPV perpetration in the past year [1.9% (95%CI = 1.4-2.5)], and every one-point increase in their gender equality belief scale score [indicative of less gender equitable beliefs] was associated with 2.1 times greater odds of perpetrating past-year IPV (AOR: 2.14, 95%CI 1.61-2.86). Conclusions Findings support prior research indicating that patriarchal beliefs reinforce men's violence against women in relationships and signal a need for violence prevention efforts focused on boys and men to that can include normative belief shifts related to women's capacities.